Corn starch processing wastewater treated by a full-scale expanded granular sludge bed reactor and comprehensive analysis of microbial community at low and high organic loading rate. Issue 1 (May 2021) - Yan, H H; Han, L; Yin, Q; Guo, X Y; Nian, Y G
Abstract: In this study, a full-scale expanded granular sludge bed (EGSB) reactor treating corn starch processing wastewater (CSPW) was monitored. The efficacy and microbial diversity of sludge granules were thoroughly investigated. The results demonstrated that 90.7% of the average chemical oxygen demand (COD) removal efficiency was observed to be in the range of an organic load rate (OLR) of 1.3 to 18.7 g COD/L·d. The Illumina MiSeq sequencing revealed that Proteobacteria, Bacteroidetes, Acidobacteria and Euryarchaeota were the dominant phyla. Acetoclastic and hydrogenotrophic methanogens were shown to play functions in methane production and the maintenance of the granular sludge under high and low OLR operation conditions, respectively. Syntrophorhabdus, Syntrophus and Candidatus Cloacimonas had the correlation with the transformation of the proteinaceous subtances into VFAs. The results will guide development of microbial management methods to improve the process stability of EGSB treating CSPW.